Large Meteorite Impacts and Planetary Evolution; II 1999
DOI: 10.1130/0-8137-2339-6.317
|View full text |Cite
|
Sign up to set email alerts
|

Impact diamonds in the Suevitic Breccias of the Black Member of the Onaping Formation, Sudbury Structure, Ontario, Canada

Abstract: Eleven samples (mostly of the Onaping Formation) from the 1.85-Ga Sudbury impact structure were examined with respect to their carbon phases. Six impact diamonds, <0.6 mm in diameter, were discovered in two samples of the Black Member of the Onaping Formation. These diamonds occur in a variety of colors, are cubic, and are generally friable due to inclusions and polycrystallinity. In one case, the hexagonal phase lonsdaleite was detected. According to transmission electron microscopy analyses, the mean grain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The source of carbon for the fullerenes at Sudbury has not been successfully explained yet, though it seems that the target rocks contained little carbon (Heymann et al 1999). This suggestion was made upon a remarkable observation that "shock metamorphosed carbons," such as chaoite and diamond, are very rare at Sudbury (Masaitis et al 1997). Also the distribution of fullerenes in Sudbury is very heterogeneous (Heymann et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of carbon for the fullerenes at Sudbury has not been successfully explained yet, though it seems that the target rocks contained little carbon (Heymann et al 1999). This suggestion was made upon a remarkable observation that "shock metamorphosed carbons," such as chaoite and diamond, are very rare at Sudbury (Masaitis et al 1997). Also the distribution of fullerenes in Sudbury is very heterogeneous (Heymann et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The gray, green, and black members contain recrystallized glass fragments (Dressler et al 1996). Masaitis et al (1997) observed shockproduced diamonds in the breccias of the black member.…”
Section: Introductionmentioning
confidence: 99%
“…Siebenschock et al, 1998) failed to find either cubic diamond or SiC at the Ries. Silicon carbide has also been reported from the Onaping Formation at the Sudbury impact structure (Masaitis et al, 1999). It is associated with impact diamonds that are a mixture of cubic diamond and hexagonal lonsdaleite from the solid-state transformation of precursor graphite in carbonaceous Huronian target lithologies by shock compression.…”
Section: Other Structuresmentioning
confidence: 97%
“…Siebenschock et al 1998) failed to find either cubic diamond or SiC at the Ries. Silicon carbide, however, has been reported from the Onaping Formation at the Sudbury impact structure (Masaitis et aL 1999). In this location, it is associated with impact diamonds that are a mixture of cubic diamond and hexagonal lonsdaleite, resulting not from chemical vapour deposition but from solid-state transformation by shock of precursor graphite.…”
Section: Syngenetic Depositsmentioning
confidence: 98%